PELATIHAN PEMBUATAN GAME EDUKASI DAN ANIMASI KEPADA SISWA PAKET B PKBM CIPTA TUNAS KARYA - Sholihin, Sholihin; Nurjaya2, Nurjaya2 (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Information technology has become very important in the world of education today. It not only functions as a medium for communication and information in school activities, but also serves as an interesting learning medium for students. Some examples of the use of information technology as learning media are videos. Information technology-based media must be chosen carefully because it makes students more interested and makes them more involved in the lesson.Information technology-based learning media is very good to apply during learning because students are more interested in technology-based media so that students will be more enthusiastic during learning activities, especially learning for children, educational game technology and animation, by carrying out the concept of fun learning. (learning while playing). Educational games can also be said to be computer games created using programming and animation techniques. In general, video games provide a reward system, for example a score that is calculated based on the level of success achieved in completing tasks in the game. Video games are liked by many children and adults, apart from being intended to entertain, games can also help attract interest. Keywords: Learning Media, Games, Educational games